Petri Net Based Modelling of a Career Syllabus - Carvajal-Schiaffino, R (Agora University, 2014)
A syllabus is a set of courses, their prerequisites and a set of rules defining the continuance of a student in an academic program. The manual verification of the possible contradictions between prerequisites and the set of rules is a difficult task due to the large number of possible cases. In this article we present the different stages in the verification of a syllabus, its modelling and analysis using Petri nets, and suggested ways in which this may be used by the university administration in the decision making process. © 2006-2014 by CCC Publications.